New approach on the modification of liquid natural rubber production using microwave technique - Mohamad Shahrul Fizree Idris,; Siti Fairus M. Yusoff,; Wan Nur Aini Wan Mokhtar, (Penerbit Universiti Kebangsaan Malaysia, 2019)
High-speed synthesis using microwave technique has attracted considerable intentions among researchers as it provides an efficient time of doing reactions. Modification of liquid natural rubber (LNR) via hydrogenation using of 2,4,6-trimethylbenzenesulfonylhydrazide (MSH) produced hydrogenated liquid natural rubber (HLNR). The results showed that microwave-assisted hydrogenation of LNR was experimentally found to give expected product in a short time (10–20 min). The structure of products was characterized by Fourier-transform infrared (FTIR) and the percentage of hydrogenation was determined from the 1H-NMR spectrum. The highest hydrogenation percentage of HLNR for hydrogenation of LNR by microwave heating were obtained; an LNR hydrogenation percentage of 41.18% at a MSH:LNR weight ratio of 1.5:1, a microwave power of 600 W and a reaction time of 20 min. Diimide molecules have been generated more quickly at microwave frequencies and yield HLNR in a shorter time compared to reflux heating method.